Outcomes of Human Papilloma Virus Vaccination in a Private Women Health Clinic in Lebanon - Muhieddine Seoud; Iman Jaafar; Rayan Ghanem; Christiane Soubhieh; Abdallah Adra; Anwar Nassar; Ali Khalil (Obstetrics and Gynecology International)
Objectives. The study aims to report on the feasibility and associated adverse events of HPV-Vaccination (HPVV) in a private clinic setting in Lebanon and, when available, the results of subsequent cervical cancer screening. Methods. Opportunistic HPV vaccination is offered at the Women’s Health Center of the AUBMC. We retrospectively reviewed the patients’ demographic data, the incidence of adverse events, and their cytological screening. Results. A cohort of healthy women (n = 1013) aged 26.2 years (12–54 years) were opportunistically vaccinated with one of two HPV vaccines; 845 (83.4%) received the quadrivalent vaccine (Q4V), and 151 (14.1%) received the bivalent vaccine (B2V). The majority (75.8%) received three doses while 16% received two doses. Out of these women, 26.3% (267) became sexually active postvaccination (NS2), whereas 17% (174) were sexually active prior to vaccination (SA) and the rest 57% (572) reported no sexual activity (NS1). Among the SA group, 26% (46/147) presented with abnormal cytology at time of vaccination. As for the NS2 women, 5% (14/267) had subsequently abnormal screening within 37 (12–103) months following vaccination. Conclusions. In this observational study, we report the successful introduction of HPVV with negligible adverse events. The incidence of abnormal cervical cytology was low among our patients.